Kesiapan Menikah Perempuan Emerging Adulthood Etnis Arab - Nurlita Endah Karunia; Salsabilah Salsabilah; Sri Wahyuningsih (Jurnal Psikologi Islam dan Budaya, 2018)
Emerging adult from Arabic-Muslim families, have fulfilled expectations of their families to married immediately. Marriage readiness are needed to evaluate the degree of readiness into marriage life The aim of this study is to explore marriages readiness of emerging adult in Arabic culture. Data were collected from 118 women between 18 – 25 years old. Most of participants have high degree of marriage readiness. In addition, most of participants have greater readiness based on several criteria: moral, contextual-social, and marital-life skilsl. The other hands, participants evaluated their readiness quite well on financial and emotional criteria. The results indicate that social-cultural, religion, and emotional maturity factors became basic evaluation of marriage readiness in emerging adult.